PENGELOLAAN KEGIATAN BELAJAR MASYARAKAT (PKBM) DI KOTA BENGKULU (Studi Pada PKBM Sriwijaya Sawah Lebar Kota Bengkulu) - Muhammad Nursamsi; Riskan Riskan; Parlan Parlan (UNIB Press, Universitas Bengkulu, 2019)
The purpose in this research are to know about planning, how to organize, how to realization and doing control from centre of society learning activity ( pusat kegiatan belajar masyarakat ) Sriwijaya. In this research use method qualitative with technique of collection the data are interview, observation and documentation. The subject has been choose is managment of PKBM Sriwijaya, there are consists of the leader is Mr. Ralin MS Gumay and the treasurer Mrs. Umi Yanti. To proving the validity of data, the researcher do to checking the data with triangulation, there are triangulation source, triangulation technique, and triangulation of time. The data has been analyze with 3 step, there are, reduction of data, presentation of data, and last is take a conclusion. The result from this research are found, first is planning, formulate the perspective and mission, prepare the tools and labor done in preparation. Second, how to organize, PKBM sriwijaya have management organization there are consists of builder, leader, secretary, and treasurer. Third is realization, in doing program activity, PKBM Sriwijaya use fund by society, and the curriculm they are use is from tbe goverment. Fourth, for doing control from manager of PKBM Sriwijaya, its about direct or not, the manager too, doing the controling the tutor will be become an object of evaluation. Key words : Managment, Centre of society learning activity